Entomopathogens Isolated from Invasive Ants and Tests of Their Pathogenicity - Maria Fernanda Miori de Zarzuela; Luis Garrigós Leite; José Eduardo Marcondes; Ana Eugênia de Carvalho Campos (Psyche: A Journal of Entomology)
Some ant species cause severe ecological and health impact in urban areas. Many attempts have been tested to control such species, although they do not always succeed. Biological control is an alternative to chemical control and has gained great prominence in research, and fungi and nematodes are among the successful organisms controlling insects. This study aimed to clarify some questions regarding the biological control of ants. Invasive ant species in Brazil had their nests evaluated for the presence of entomopathogens. Isolated entomopathogens were later applied in colonies of Monomorium floricola under laboratory conditions to evaluate their effectiveness and the behavior of the ant colonies after treatment. The entomopathogenic nematodes Heterorhabditis sp. and Steinernema sp. and the fungi Beauveria bassiana, Metarhizium anisopliae, and Paecilomyces sp. were isolated from the invasive ant nests. M. floricola colonies treated with Steinernema sp. and Heterorhabditis sp. showed a higher mortality of workers than control. The fungus Beauveria bassiana caused higher mortality of M. floricola workers. However, no colony reduction or elimination was observed in any treatment. The defensive behaviors of ants, such as grooming behavior and colony budding, must be considered when using fungi and nematodes for biological control of ants.